Paternity and egg cannibalism in the ringlegged earwig Euborellia annulipes (Dermaptera: Anisolabididae). Issue 3 (6th June 2019) - Jacobs, Anne C.; Stigall, Tyler
Abstract: Cannibalism is a common occurrence in nature, and many cannibals prey on relatively small and defenseless life stages, such as eggs or young juveniles. Such behavior provides many benefits to the cannibal, but cannibalistic individuals also face risks, including the cost of decreasing their inclusive fitness by eating close relatives such as siblings or offspring. This risk can be mitigated if cannibals can recognize and avoid preying on kin. Here, we tested whether male ringlegged earwigs Euborellia annulipes avoid cannibalizing eggs that they had sired. In this species, females care for their own eggs, but males provide no care and frequently prey upon eggs. We found that when presented with an unguarded clutch of eggs, male earwigs nearly always cannibalized some eggs, but that the proportion of eggs eaten was smaller if the male had sired the clutch. This suggests that males can distinguish between their own offspring and unrelated offspring and that they avoid harming their kin. Abstract : We tested whether male ringlegged earwigs could recognize and avoid cannibalizing their own eggs. Males of this species do not provide parental care and frequently prey upon eggs. We found that males placed with eggs they had sired ate proportionally fewer of those eggs than males placed with an unrelated clutch.